2011
DOI: 10.3171/2011.1.jns10884
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of adverse outcomes by blood glucose level after endovascular therapy for acute ischemic stroke

Abstract: Failure of blood glucose values to decrease in the first 48 hours after AIS intervention correlated with poor 90-day outcomes in nondiabetic patients. The BRANCH scale shows promise as a simple prognostication tool after endovascular therapy for AIS, and it merits prospective validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…4,10,14,29,35,43,,45,49,54 Of them, one reported a positive association with favorable outcome but not with excellent outcome. 14 Regarding mortality (11 studies, n=19979), an increase risk of death associated with higher AGL was reported in 6 studies (n=18940) 4,10,14,24,35,45,49 which remained significant after adjustment in 5 studies. Regarding sICH (18 studies, n=23794), an increase risk associated with higher AGL was reported in 7 studies (n=19659) 5,32,37,40,49,53,55 which was significant in multivariate analysis for 3 studies (n=16647).…”
mentioning
confidence: 98%
“…4,10,14,29,35,43,,45,49,54 Of them, one reported a positive association with favorable outcome but not with excellent outcome. 14 Regarding mortality (11 studies, n=19979), an increase risk of death associated with higher AGL was reported in 6 studies (n=18940) 4,10,14,24,35,45,49 which remained significant after adjustment in 5 studies. Regarding sICH (18 studies, n=23794), an increase risk associated with higher AGL was reported in 7 studies (n=19659) 5,32,37,40,49,53,55 which was significant in multivariate analysis for 3 studies (n=16647).…”
mentioning
confidence: 98%
“…According to previous studies, risk factors for ICH after ER include atrial fibrillation, 15,16) diabetes mellitus/hyperglycemia, 1,15,17) old cerebral infarction of the basal ganglia, 18) and leukoaraiosis. 19) Although the oral administration of anticoagulants prior to onset was also a risk factor in the present study, its contribution to ICH after ER was controversial in previous studies.…”
Section: Background Factors Before Onsetmentioning
confidence: 99%
“…8,38,46 Another important modifiable risk factor is glucose control. 9,35 Hyperglycemia is responsible for blood-brain barrier damage through increased production of lactic acid and free radicals, as well as direct damage to the lipid-rich neuronal membrane. 30 The desired range of blood glucose values is 80-140 mg/dl.…”
Section: Clinical and Laboratory Predictorsmentioning
confidence: 99%